Cystic Hygroma Is Particularly Concerning When Identified During The First Trimester - Hu Shi Xuan (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2025)
Cystic hygroma is a congenital condition marked by benign cysts resulting from lymphatic system abnormalities, comprising approximately 6% of all benign lesions in infancy or early childhood. This case report details a 24-year-old G3A1E1 woman with a history of induced abortion and ectopic pregnancy, diagnosed with fetal cystic hygroma at 12 weeks and 4 days of gestation. Obstetric ultrasonography identified a single, viable, intrauterine fetus exhibiting a distinct thin-walled cystic lesion with many internal septations located in the occipital region, spreading to the thorax, alongside a nuchal translucency measurement of 9 mm. The patient received counseling for medical termination of pregnancy and then underwent an induced abortion. Cystic hygroma, particularly when identified in the first trimester, is frequently linked to chromosomal anomalies and adverse prognoses. Research indicates that the overall survival rate for embryonic cystic hygroma is 10%, and the prognosis remains uncertain until the fetus reaches 26 weeks of gestation. Early identification of cystic hygroma using prenatal ultrasonography facilitates prompt intervention and informed decision-making. This example illustrates the importance of early prenatal screening and detection of fetal defects, as well as the necessity for a multidisciplinary approach in addressing intricate obstetric cases. Additional genetic counseling and testing could be advantageous for the patient in strategizing future pregnancies